Photostabilization of polyethylene by a hindered amine light stabilizer in blooming conditions and impact of MDO processing. (September 2021) - Christmann, Julien; Gardette, Jean-Luc; Pichon, Gérard; Bouchut, Bruno; Therias, Sandrine
Highlights: Solubilisation of bloomed HALS Tinuvin 770® occurs when increasing the temperature. Bloomed HALS might then efficiently stabilize PE in accelerated photoageing. This effect raises the issue of representativeness of accelerated ageing. Machine Direction Orientation process reduces the amount of bloomed HALS. Abstract: The effect of Machine Direction Orientation (MDO) processing on the photostabilization of LLDPE samples containing Tinuvin® 770 was studied. The amount of Tinuvin® 770 in the processed samples was deliberately chosen at a level higher than the reported solubility at ambient temperature for two main reasons: the first reason was to assess the equilibrium between the soluble and nonsoluble forms of this additive and the impact of the MDO process, and the second was to demonstrate the role of a higher temperature in accelerated artificial photoaging on the protective role played by the nonsoluble part. The results reported in this article show that at room temperature, a nonnegligible amount of Tinuvin® 770 precipitates at the surface, which is commonly termed blooming. However, the additive that bloomed at the surface can be dissolved within the polymer with increasing temperature, which is the case in the conditions of accelerated artificial photoaging but not the case of natural outdoor weathering. Such physical phenomena are responsible for a possible bias brought by temperature during accelerated photoaging, which can affect aging tests. This questions the representativeness of accelerated aging at higher temperatures for polymers containing a blooming stabilizer.